Patient-provider experiences with chronic non-communicable disease care during COVID-19 lockdowns in rural Uganda: A qualitative analysis - Olds, Peter K.; Nuwagaba, Gabriel; Obwoya, Paul S.; Nuwagira, Edwin; Haberer, Jessica E.; Okello, Samson (Plos one, 2023)
Non-communicable diseases (NCDs) are a growing health burden in Sub-Saharan Africa and especially Uganda, where they account for over one third of all deaths. During the COVID-19 pandemic, public health control measures such as societal “lockdowns” had a significant impact on longitudinal NCD care though no studies have looked at the lived experience around NCD care during the pandemic. Our objective was to understand the experience of NCD care for both patients and providers in southwestern Uganda during the COVID-19 pandemic. We conducted in-depth, in-person qualitative interviews with 20 patients living with hypertension, diabetes, and/or cardiac disease purposefully selected from the outpatient clinics at Mbarara Regional Referral Hospital and 11 healthcare providers from public health facilities in Mbarara, southwestern Uganda. We analyzed transcripts according to conventional content analysis. We identified four major themes that emerged from the interviews; (1) difficulty accessing medication; (2) food insecurity; (3) barriers to the delivery of NCD clinical care and (4) alternative forms of care. Pre-existing challenges with NCD care were exacerbated during COVID-19 lockdown periods and care was severely disrupted, leading to worsened patient health and even death. The barriers to care were exacerbations of underlying systemic problems with NCD care delivery that require targeted interventions. Future work should leverage digital health interventions, de-centralizing NCD care, improving follow-up, providing social supports to NCD patients, and rectifying supply chain issues.
Keywords: Non-communicable diseases; Uganda; Deaths; COVID-19; Patients